Stability of problem eating behaviors and weight loss trajectories following bariatric surgery: a longitudinal observational study - Conceição, Eva Martins (2017)
Background: The literature is rather mixed regarding the stability and the role of pre- and postoperative problematic eating behaviors (PEBs) on weight outcomes after bariatric surgery.Objectives: To investigate the stability of loss of control (LOC) eating and picking and/or nibbling from pre- to postoperative assessments, and to investigate whether pre- and postoperative PEBs are predictors of different weight loss trajectories.Setting: Central Hospital, University, Portugal.Methods: This longitudinal study assessed LOC eating and picking and/or nibbling before and approximately 2 years after laparoscopic adjustable gastric banding or Roux-en-Y gastric bypass through face-to-face interviews and 2 self-report measures. Weight across follow-up time was retrieved from hospital charts. Of the 130 patients invited to participate in the study, 100 were assessed preoperatively, and of these, 61 were also assessed postoperatively.Results: Frequency of PEBs is similar pre- and postoperatively (37.7% and 45.9%, respectively) (McNemar chi(2) P = .832). Yet, about 40% ceased preoperative PEBs. Those with LOC preoperatively were more likely to develop picking and/or nibbling postoperatively (McNemar chi(2) P < .05). About 39.5% developed PEBs de novo after surgery. The presence of PEBs postoperatively was a significant predictor of different weight loss trajectories after both laparoscopic adjustable gastric banding and Roux-en-Y gastric bypass. Worse weight loss outcomes were found particularly at 17-20 months postsurgery. Preoperative PEBs were not a significant predictor.Conclusions: Our data do not support the stability of all PEBs across time, highlighting that the absence of preoperative PEBs does not preclude an unfavorable weight loss outcome after surgery. Postoperative but not preoperative PEBs are predictors of poorer weight loss trajectories after surgery. (C) 2017 American Society for Bariatric Surgery.